Self-Evaluation Of Educational And Administrational Supervisors In The City Of Zakho - Shokry, Bewar T.; Mohammed, Nasraldin I. (Humanities Journal of University of Zakho, 2017)
The aim of study is to testify the statistical hypotheses concerning the significant differences among supervisors in the city of Zakho according to the variables of the study in the academic year (2015/2014) in self-evaluation. The population and the sample of the research consists of (28) supervisors in the city of Zakho. The researchers used the interview and questionnaire which includes of (31) items. The results of the research showed that supervisors have a significant meaningful self- evaluation toward themselves and their function; also there is no statistical significant differences among them according to the variables of gender, diploma, age and years of service. The study presented some suggestions and recommendations in the light of results.